(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The Indian automobiles industry is witnessing a defining moment. More than six decades after its inception, the industry is on the threshold of a major leap forward, increasing scales and depth, considerable product variation and increasing acceptability of Indian products in regional and global markets are largely driving this surge. India is fast emerging as a credible and the large outsourcing hub for automobiles and auto component industry. In this paper the automobile industry has been divided into 3 eras: - Antique, Classic and Modern Era which also divided into sub-eras. It also focuses on the growth and performance of automobiles industry in India.